2018
DOI: 10.1590/1678-7757-2017-0630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-surgical periodontal therapy on the degree of gingival inflammation and stress markers related to pregnancy

Abstract: ObjectivesThe purpose of this study was to determine the impact of nonsurgical periodontal therapy considering the salivary stress-related hormone and cytokine levels in the gingival crevicular fluid (GCF) on pregnant and nonpregnant women.Material and MethodsThirty non-pregnant (control group) and 30 pregnant women (test group) that met the study inclusion criteria were chosen. Only participants with gingivitis were included. Clinical data and samples of GCF and saliva were collected at baseline and after per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
8
0
4
Order By: Relevance
“…Além da suscetibilidade à inflamação decorrente de alterações moleculares nos níveis de mediadores do FCG, pode haver o aumento da suscetibilidade individual à infecção, com a inibição da função de linfócitos, macrófagos e monócitos. As alterações hormonais e fisiológicas podem também aumentar os níveis de estresse levando ao aumento dos níveis de hormônios relacionados ao estresse que podem implicar na produção de citocinas próinflamatórias e afetar a DP (20). Foi observado que 34% das gestantes apresentaram código OHIP-14 acima da média, o que pode estar relacionado a fatores como ausência de dentes, presença de sangramento ou cálculo dentário e hábito de fumar.…”
Section: Resultsunclassified
“…Além da suscetibilidade à inflamação decorrente de alterações moleculares nos níveis de mediadores do FCG, pode haver o aumento da suscetibilidade individual à infecção, com a inibição da função de linfócitos, macrófagos e monócitos. As alterações hormonais e fisiológicas podem também aumentar os níveis de estresse levando ao aumento dos níveis de hormônios relacionados ao estresse que podem implicar na produção de citocinas próinflamatórias e afetar a DP (20). Foi observado que 34% das gestantes apresentaram código OHIP-14 acima da média, o que pode estar relacionado a fatores como ausência de dentes, presença de sangramento ou cálculo dentário e hábito de fumar.…”
Section: Resultsunclassified
“…Turki. (Yarkac et al, 2018). Tedapat sejumlah 9 artikel jurnal yang menjadi bahan review dalam studi laporan sistematik review ini.…”
Section: Ibu Nifasunclassified
“…The very first application of CgA was to detect neuroendocrine tumors (NETs), as illustrated by a pioneering study in 1986 that demonstrated a sensitivity of 81% and a specificity of 100% for the diagnosis of a pheochromocytoma [1]. Since then, several biomarkers have been developed and are commercially available [20,149,150].…”
Section: Cga As Current Biomarkers On the Marketmentioning
confidence: 99%